Perspectiva metafísica de la educación - Mescua, Augusto César (2015)
This article aims to sustain an ontological definition of education. Education as an entity (true story), finite being (made compound), accidental being (contingent) essence (which is itself), shape (quality) and habit (constant readiness). I intended to support education as perfectible process of man’s potentialities in the exercise of human virtues as usual aspects of their specific operations. In conclusion, from this perspective, an active pedagogical approach that aims to consider the student as an actor and actor, composer and creator of his own life, as opposed to traditional pedagogies that support the concept of man as passive, requiring only shows nurture their intelligence from outside, characterized merely as a passive entity.